The Influence of Product Quality, Brand Image, and Price Perception on Purchase Decisions at Starbucks Coffee Surabaya - Faza Nailinajiyah Darmayanti; Siti Aminah (Indonesian Journal of Business Analytics, 2023)
This study entitled "The Influence of Product Quality, Brand Image, and Price Perception  on Purchasing Decisions (Study at Starbucks Coffee Surabaya)" with the aim of knowing how much influence product quality, brand image, and price perceptions have on purchasing decisions at Starbucks Coffee in Surabaya. The method used in this study is a type of quantitative method with purposive sampling technique. The research sample was 98 people. This study collected data through questionnaires that were distributed to consumers with the criteria of being over 17 years old and having made a purchase at Starbucks Coffee in Surabaya. The analytical tool used in this study is the Partial Least Square (PLS) model. The results of this study indicate that product quality has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, and Price Perception  has a positive and significant effect on purchasing decisions.